Ian Burton, W. Kates y Gilbert F. White. The environment as hazard. Nueva York : Oxford University Press, 1978. 240 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
IAN BURTON, W. KATES, y GIBBERTF. WHTTE. The Environment as Hazard, Oxford University Press, Nueva York, 1978.